2022
DOI: 10.1126/sciadv.abn4580
|View full text |Cite
|
Sign up to set email alerts
|

CO oxidation by Pt 2 /Fe 3 O 4 : Metastable dimer and support configurations facilitate lattice oxygen extraction

Abstract: Heterogeneous catalysts based on subnanometer metal clusters often exhibit strongly size-dependent properties, and the addition or removal of a single atom can make all the difference. Identifying the most active species and deciphering the reaction mechanism is extremely difficult, however, because it is often not clear how the catalyst evolves in operando. Here, we use a combination of atomically resolved scanning probe microscopies, spectroscopic techniques, and density functional theory (DFT)–based calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…In the process of CO oxidation catalyzed by Pt/Fe 3 O 4 model catalyst, the dynamically formed Pt 2 dimer was conducive to the extraction of oxygen from the carrier lattice at 525 K (252 °C) to promote CO oxidation (see Figure ). [ 47 ] The initial state of the Pt/Fe 3 O 4 (001) monoatomic catalyst was characterized by scanning tunneling microscopy (STM) and noncontact atomic force microscopy (ncAFM) (see Figure 23a–c), which confirmed the geometry of (PtCO) 2 determined by DFT calculations and allowed direct imaging of individual CO molecules adsorbed on sub‐nanoclusters (see Figure 23d,e). The researchers found that CO oxidation occurs in a metastable (PtCO) 2 configuration, which is the key intermediate configuration of Pt/Fe 3 O 4 (001) catalyst during the catalytic reaction at high temperature.…”
Section: Structural Types Of Diatomic Catalystsmentioning
confidence: 66%
See 4 more Smart Citations
“…In the process of CO oxidation catalyzed by Pt/Fe 3 O 4 model catalyst, the dynamically formed Pt 2 dimer was conducive to the extraction of oxygen from the carrier lattice at 525 K (252 °C) to promote CO oxidation (see Figure ). [ 47 ] The initial state of the Pt/Fe 3 O 4 (001) monoatomic catalyst was characterized by scanning tunneling microscopy (STM) and noncontact atomic force microscopy (ncAFM) (see Figure 23a–c), which confirmed the geometry of (PtCO) 2 determined by DFT calculations and allowed direct imaging of individual CO molecules adsorbed on sub‐nanoclusters (see Figure 23d,e). The researchers found that CO oxidation occurs in a metastable (PtCO) 2 configuration, which is the key intermediate configuration of Pt/Fe 3 O 4 (001) catalyst during the catalytic reaction at high temperature.…”
Section: Structural Types Of Diatomic Catalystsmentioning
confidence: 66%
“…[125] Further density functional theory calculations show that the electron redistribution and bandgap narrowing caused by the bonded FeN 4 and CuN 3 moieties enhance the electron conductivity and enhance the bonding interaction between the *COOH intermediate and the Fe center, thus reducing the overall reaction barrier and promoting the generation of CO. [126] The prepared Fe/CuNC diatomic catalyst has (a-e) Reproduced with permission. [47] Copyright 2022, Science.…”
Section: Mof Derivative Methodsmentioning
confidence: 99%
See 3 more Smart Citations